PENGEMBANGAN BAHAN AJAR QAWAID BAHASA ARAB BERBASIS MIND MAP UNTUK TINGKAT PERGURUAN TINGGI - Zakiyah Arifa, Dewi Chamidah (lp2m-uin malang, 2011)
The research was motivated by the difficulty of students studying Qawaid considered difficult and complex. The research aims to develop teaching materials based Arabic qawaid mind map and find out the learning process of students by using teaching materials based Arabic qawaid mind map for the college level. This research method using the R D (research and development). The results of this study were 1. development of teaching materials based Arabic qawaid mind map for the college-level teaching materials presented in the form of maps with different patterns of shape and color illustrations that have a major theme (primary) connected to the theme of the derivative and connected with each other accompanied by examples . 2. Use of these materials indicate that the Arabic language teaching materials qawaid based mind map can improve learning outcomes of students with average 78.59 / B +, and increase motivation to learn qawaid.Key words: bahan ajar, qawaid bahasa Arab, mind map